INFORMATION AND COMMUNICATION TECHNOLOGIES AS A TOOL FOR INCREASING THE EFFICIENCY OF PRINTING COMPANIES’ ECONOMIC ACTIVITY - MAKATORA, Alona; MAKATORA, Dmytro; ZENKIN, Mykola; KUBANOV, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In order to increase the efficiency of economic activity of printing companies, the authors of the study have identified the following features and promising directions: reorientation of management tasks for the development of printing companies in order to ensure their competitiveness; determination of strategic directions of development of printing companies; optimisation of the appropriate level of information, resource and organisational support of printing companies for the successful implementation of development strategies; diversification of activities of printing enterprises; corporatisation of printing enterprises; ensuring investment development of printing industry enterprises. The implementation of strategies aimed at optimising processes, reducing costs, using advanced technologies and increasing the efficiency of interaction with consumers is the reorientation of management tasks for the development of printing companies in order to ensure their competitiveness. The strategic directions for the development of printing companies include: European integration, improvement of product quality in accordance with international standards, use of information technology to optimise production processes, innovation, expansion of production links, environmental friendliness and solving the problem of qualified personnel. The successful implementation of development strategies depends on optimising the appropriate level of information, resources and organisational support for the activities of printing companies. Information support is concerned with determining strategic directions through the analysis of internal and external information. The focus of resource support is on the efficient management of resources for the achievement of production efficiency. Organisational support involves creating an effective structure and motivating staff. Diversifying printing businesses in the current environment requires adopting the latest technologies and using information and communication technologies. This makes it possible to expand the range of products, increase the efficiency of production, optimise management and improve customer relations. The corporatisation of printing companies is important for business development, enabling companies to consolidate, implement large projects and expand markets. The integration of ICT contributes to the optimisation of production processes, the improvement of management efficiency and the creation of competitive advantages for printing companies. Using ICT in the printing industry plays a key role in increasing the attractiveness of companies to invest. The integration of ICT enables the optimisation of internal processes. It reduces costs, develops innovation and attracts new investors.